2004
DOI: 10.2170/jjphysiol.54.137
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging on Somatocardiac Reflexes in Anesthetized Rats

Abstract: Cardiac function is homeostatically regulated in response to internal and external environmental changes. It is well known that, in the elderly, cardiac function is well maintained at rest, but its ability to adjust to environmental changes is reduced compared to younger individuals [1]. For example, the cardiac response to changes in blood pressure (baro-reflex) decline with advancing age [2,3] as a result of reduced sensitivity of baroreceptors [4][5][6].Cardiac responses to changes in the external environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
3
4
0
Order By: Relevance
“…The present study is the first to demonstrate that cardiac sympathetic A-and C-reflexes are evoked by electrical stimulation applied to somatic afferents in aged rats as in adult ones. This result is consistent with a report by Suzuki et al [9] that showed the response of cardiac sympathetic nerve activity to noxious pinch stimulus in 24-27-and 32-36-month-old rats was not different from in 4-7-monthold rats. Further, we examined the effect of touch on the evoked somato-cardiac sympathetic reflexes in aged rats and found that reflex discharges were not inhibited by touch in most of the rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study is the first to demonstrate that cardiac sympathetic A-and C-reflexes are evoked by electrical stimulation applied to somatic afferents in aged rats as in adult ones. This result is consistent with a report by Suzuki et al [9] that showed the response of cardiac sympathetic nerve activity to noxious pinch stimulus in 24-27-and 32-36-month-old rats was not different from in 4-7-monthold rats. Further, we examined the effect of touch on the evoked somato-cardiac sympathetic reflexes in aged rats and found that reflex discharges were not inhibited by touch in most of the rats.…”
Section: Discussionsupporting
confidence: 93%
“…An initial dose of urethane (0.9-1.1 g/kg i.p.) was based on a previous study [9], and experimental methods were as described previously [3]. Arterial blood pressure and heart rate were continuously measured using a catheter placed in the carotid artery.…”
Section: Methodsmentioning
confidence: 99%
“…Resting HR and cardiac sympathetic nerve activity in spinalized rats were lower than those in CNS-intact rats, as we had reported previously [11,13]. CRD stimulations of 60 and 80 mmHg did not induce a significant change in the HR and cardiac sympathetic nerve activity in these animals, suggesting that the reflex center that mediates CRD-induced bradycardia is supraspinal in its location.…”
Section: Resultssupporting
confidence: 71%
“…With the rats in a prone position, the cardiac sympathetic nerves were dissected free following the removal of the second costal bone, as described previously [11,12], and their neuronal activity was amplified using a preamplifier (time constant 0.01 s; S-0476, Nihon Kohden, Tokyo) and sampled using an analog-to-digital converter (PowerLab/8, AD Instruments, Australia) at a rate of 2,000 samples/s that was rectified and integrated every 5 s. The signal recorded at the end of the experiment (after the rat had died) was set as the background noise. The value of the nervous discharge was calculated by subtracting the background noise from the recorded value for statistical analysis [13].…”
Section: Methodsmentioning
confidence: 99%
“…One characteristic of somatocardiovascular reflexes is that evoked responses differ depending on the type of stimulation. For example, a strong pinch of the skin (Kimura et al, 1995; Sato et al, 1997; Suzuki et al, 2004) and noxious thermal stimulation (Kaufman et al, 1977) generally induce tachycardiac and pressor responses. In contrast, brushing and non-noxious thermal stimulation do not lead to heart rate (HR) responses or provide only a small response (Kaufman et al, 1977; Sato et al, 1997).…”
Section: Introductionmentioning
confidence: 99%